Integration of spatial and temporal models to predict extreme water table depths - Manzione, Rodrigo Lilla; Marcuzzo, Francisco Fernando Noronha; Wendland, Edson Cezar (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate extreme water table depths in a watershed, using methods for geographical spatial data analysis. Groundwater spatio‑temporal dynamics was evaluated in an outcrop of the Guarani Aquifer System. Water table depths were estimated from monitoring of water levels in 23 piezometers and time series modeling available from April 2004 to April 2011. For generation of spatial scenarios, geostatistical techniques were used, which incorporated into the prediction ancillary information related to the geomorphological patterns of the watershed, using a digital elevation model. This procedure improved estimates, due to the high correlation between water levels and elevation, and aggregated physical sense to predictions. The scenarios showed differences regarding the extreme levels – too deep or too shallow ones – and can subsidize water planning, efficient water use, and sustainable water management in the watershed.